The dark half [videorecording (DVD)] - Romero, George A.; Harris, Julie, 1925-2013; Hutton, Timothy, 1960-; Rooker, Michael, 1955-; King, Stephen, 1947- (MGM, 2026)
Horror writer Thad Beaumont hopes to distance himself from his murder novels and from George Stark, the name he has used to anonymously author them. To achieve this, he cooks up a murder of his own: a publicity stunt that should lay Stark to rest forever. But when the people around him are found gruesomely slain and his own fingerprints dot the crime scenes, Beaumont is dumbfounded until he learns that Stark has taken on a life of his own and begun a gruesome quest for vengeance!